Impact of perceived corporate social responsibility on attitudes and behaviors of pharmacists working in MNCs. Issue 4 (13th November 2017) - Khaleel, Muhammad; Chelliah, Shankar; Rauf, Sana; Jamil, Muhammad
Abstract : Purpose: This study aims to find out how corporate social responsibility (CSR) initiatives are perceived by pharmacists and how it influences employees' organizational commitment and organizational citizenship behavior (OCB) and role of perceived supervisor support in the study. Design/methodology/approach: Pharmacists of different hierarchical levels from five multinational pharmaceutical industries in Pakistan were selected as study samples. Data were collected from 136 pharmacists working in Punjab Region. PLS-SEM was used to test the hypotheses. Findings: The results from this study found that CSR was a predictor of affective organizational commitment (AOC) and OCB. AOC fully mediates the relationship between CSR and OCB. While perceived supervisory support did not moderate the relationship between AOC and OCB. Pharmaceutical firms can promote commitment toward organization and OCBs by initiating CSR activities. Research limitations/implications: This research is one of the innovative studies that empirically examine the predicting role of CSR and moderating role of perceived supervisory support on employees' attitude and behaviors in the pharmaceutical companies' context. Moreover, this research will also help the management by adopting CSR activities as core element in shaping employees attitudes and behaviors. Originality/value: It is a significant study shifting the focus of research into organizational behavior context and further influences employee's attitudes and behavior because of perceived CSR in the pharmacy industry.